BROKEN HOMES AND CHILDHOOD EXPERIENCES IN CHRISTIE WATSON’S TINY SUNBIRDS, FAR AWAY AND SADE ADENIRAN’S IMAGINE THIS - KUFONIYI , Ajibola Toluwalope; OKEKUNLE, Michael Olamide (International Journal of Arts, Languages, Linguistics and Literary Studies, 2025)
The formative years of a child are critical to their overall development, with early experiences, particularly within the family unit, playing a defining role. This study examines the portrayal of broken families and their impact on children in two selected novels: Christie Watson’s Tiny Sunbirds, Far Away and Sade Adeniran’s Imagine This. While Watson’s novel delves into the effects of infidelity on a Nigerian family, Adeniran’s work portrays the challenges faced by a young girl following her family’s relocation to Nigeria. Drawing on structural-functionalism as the theoretical framework, this study explores the emotional, psychological, and academic consequences of broken homes on children, as depicted in these texts. A review of related literature highlights gaps in existing studies, particularly concerning the specific effects of broken families on children’s development. Through qualitative textual analysis, this study identifies how the authors present these effects and underscores the broader societal implications of family instability. The findings reveal that children from broken homes are more susceptible to emotional and behavioral issues, as well as academic challenges, which ultimately hinder their growth and societal contributions. The study concludes by emphasizing literature’s role in reflecting societal issues and fostering awareness of the challenges faced by children in unstable family environments. It advocates for systemic reforms, community support, and individual empathy to mitigate these effects and nurture the potential of every child, ensuring a more equitable and stable future.